Uganda’s evolving national biosafety system: lessons from the past 30 years - Zawedde, B. M.; Kwehangana, M.; Ongu, I.; Ibanda, A. W.; Wasswa, P.; Kiggundu, A.; Mugoya, C.; Kasule, D.; Makara, A. M.; Hafashimana, D.; Ssengooba, T.; Oloka, H. K. (Frontiers in Bioengineering and Biotechnology, 2025)
Uganda has made progress towards developing a functional biosafety system. The system has evolved in the past three decades to enable substantial application of modern biotechnology in different sectors. Key informant interviews were used to capture tacit knowledge from respondents who were identified to have vast knowledge and experience of the biosafety system of Uganda in the past 30 years. Secondary data was then used to fill the gaps in the knowledge map. From the findings we were able to identify the key drivers of policy reforms that shaped the evolution of the biosafety regulatory system; policy, institutional developments, partnerships, public participation and engagements milestones that contributed to developing the biosafety system in Uganda. We discuss the lessons learnt and their implications for on-going and future biosafety policy and legal discourse. We share some strategic recommendations that we believe if implemented will enable Uganda, and other developing countries, to put in place a coordinated and evidence-based regulatory system, which is required for effective application and adoption of the current and emerging biotechnologies. Uganda’s case study is also a learning experience for countries that are in the process of establishing biosafety frameworks.